Хімічні та електрохімічні механізми взаємодії металів підгрупи міді з окисненим вугіллям - Копил, С.А. (Поверхность, 2003)
Досліджено сорбційно-електрохімічні властивості активного вугілля при взаємодії з металами підгрупи міді. Показано, що процеси взаємодії основного та кислотноговугілля з цими металами здійснюються за різними механізмами. Для оцінки впливу кисню на електронодонорні властивості вугільних матеріалів проведено квантово-хімічні розрахунки енергетичних характеристик кластерів, що моделюють поверхню активного вугілля. Показана роль кисню в процесах відновної сорбції іонів металів підгрупи міді. Sorption and electrochemical properties of active carbons have been studied in
interaction with copper metals subgroup. The processes of the interaction of basic and acid carbon materials with these metals have been shown to occur due to different mechanisms. In order to estimate the effect of oxygen on the electron-donor properties of carbon, quantum chemical calculations were carried out on energy characteristics of the clusters simulated for active carbon surface. The role of oxygen has been demonstrated in reduction sorption processes of copper metals subgroup ions.